A risk‐based approach to managing active pharmaceutical ingredients in manufacturing effluent. (18th November 2015) - Caldwell, Daniel J.; Mertens, Birgit; Kappler, Kelly; Senac, Thomas; Journel, Romain; Wilson, Peter; Meyerhoff, Roger D.; Parke, Neil J.; Mastrocco, Frank; Mattson, Bengt; Murray‐Smith, Richard; Dolan, David G.; et al.
Abstract: The present study describes guidance intended to assist pharmaceutical manufacturers in assessing, mitigating, and managing the potential environmental impacts of active pharmaceutical ingredients (APIs) in wastewater from manufacturing operations, including those from external suppliers. The tools are not a substitute for compliance with local regulatory requirements but rather are intended to help manufacturers achieve the general standard of "no discharge of APIs in toxic amounts." The approaches detailed in the present study identify practices for assessing potential environmental risks from APIs in manufacturing effluent and outline measures that can be used to reduce the risk, including selective application of available treatment technologies. These measures either are commonly employed within the industry or have been implemented to a more limited extent based on local circumstances. Much of the material is based on company experience and case studies discussed at an industry workshop held on this topic. Environ Toxicol Chem 2016;35:813–822. © 2015 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.